Dallas Smythe Today - The Audience Commodity, the Digital Labour Debate, Marxist Political Economy and Critical Theory. - Christian Fuchs (tripleC: Communication, Capitalism & Critique, 2012)
Due to the global capitalist crisis, neoliberalism and the logic of commodification of everything have suffered cracks, fissures and holes. There is a return of the interest in Marx, which requires us to think about the role of Marxism in Media and Communication Studies. This paper contributes to this task by discussing some foundations of contemporary Marxist media and communication studies, including a focus on the renewed interest in Dallas Smythe’s audience commodity category as part of the digital labour debate. Dallas Smythe reminds us of the importance of engagement with Marx’s works for studying the media in capitalism critically. Both Critical Theory and Critical Political Economy of the Media and Communication have been criticized for being one-sided. Such interpretations are mainly based on selective readings. They ignore that in both approaches there has been with different weightings a focus on aspects of media commodification, audiences, ideology and alternatives. Critical Theory and Critical Political Economy are complementary and should be combined in Critical Media and Communication Studies today. Dallas Smythe’s notion of the audience commodity has gained new relevance in the debate about corporate Internet services’ exploitation of digital labour. The exploitation of digital labour involves processes of coercion, alienation and appropriation.